2020
DOI: 10.1186/s12913-020-05865-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunization data quality of routine reports in Ho municipality of Volta region, Ghana

Abstract: Background Immunization has been an important public health intervention for preventing and reducing child morbidity and mortality over the years and coverage has increased in the past decades. However, the validity of the data from immunization coverages is usually disputed. Immunization data from health facilities show poor concordance between tallied registers and monthly reports as they are reported to higher levels of the health system. The study assessed the quality of data from routine immunization of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In most countries, target populations are estimated based on projections using old and inaccurate population census data, without applying WHO recommendations on methods for assessing target population accuracy, such as comparing estimates with alternative sources, plotting, and analyzing target populations over time, and monitoring target population growth rates [39]. Assessing immunization data quality of routine reports in Ho municipality of Volta region in Ghana, Ziema et al [40] found 20% overreporting of data on children vaccinated with BCG, DTP3 and MCV2. Reasons attributable to overreporting could be arithmetic errors during monthly data compilation or deliberate overreporting to achieve high coverage to avoid queries by higher staff levels [40].…”
Section: Discussionmentioning
confidence: 99%
“…In most countries, target populations are estimated based on projections using old and inaccurate population census data, without applying WHO recommendations on methods for assessing target population accuracy, such as comparing estimates with alternative sources, plotting, and analyzing target populations over time, and monitoring target population growth rates [39]. Assessing immunization data quality of routine reports in Ho municipality of Volta region in Ghana, Ziema et al [40] found 20% overreporting of data on children vaccinated with BCG, DTP3 and MCV2. Reasons attributable to overreporting could be arithmetic errors during monthly data compilation or deliberate overreporting to achieve high coverage to avoid queries by higher staff levels [40].…”
Section: Discussionmentioning
confidence: 99%
“…In most countries, target populations are estimated based on projections using old and inaccurate population census data, without applying WHO recommendations for methods for assessing target population accuracy, such as comparing estimates with alternative sources, plotting and analyzing target populations over time and monitoring target population growth rates [ 38 ]. Assessing the immunization data quality of routine reports in the Ho municipality of the Volta region in Ghana, Ziema and Asem [ 39 ] found data overreporting of 20% on children vaccinated with the BCG, DTP3 and MCV2. Reasons attributable to overreporting could be arithmetic errors during monthly data compilation or deliberate overreporting to achieve high coverage to avoid queries by higher staff levels [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the immunization data quality of routine reports in the Ho municipality of the Volta region in Ghana, Ziema and Asem [ 39 ] found data overreporting of 20% on children vaccinated with the BCG, DTP3 and MCV2. Reasons attributable to overreporting could be arithmetic errors during monthly data compilation or deliberate overreporting to achieve high coverage to avoid queries by higher staff levels [ 39 ]. Data quality issues leading to the over- or under-estimation of immunization coverage highlights the need to revamp the whole immunization information system.…”
Section: Discussionmentioning
confidence: 99%
“…The available information should help make decisions and solve problems until the level of problem-solving. The presence of a supervisor or a director, feedback, and improvement of human resources through training and development were parts of positive mechanisms in supporting the improvement of notification quality in order to improve their skills related to their field that the result would be helpful to make decisions in an organization (Russell, 2015;Ziema & Asem, 2020). Related to monitoring and supervising, every local clinic should directly and regularly monitor the activities in the field which a supervisor conducts, and this part became important in deciding policy related to the program of monitoring and development (Faber et al, 2009).…”
Section: Discussionmentioning
confidence: 99%